The Book of Contemplation : Islam and the Crusades - Usamah Ibn Munqidh, 1095-1188 (London Penguin, 2008)
A translation of a key medieval Arabic text that bears directly on the Crusades and Crusader society and the Muslim experience of them.
Include Index, Glossary and Notes
Keywords: Crusades -- Syria -- Usāmah ibn Munqidh, 1095-1188